THE INFLUENCE OF KARAPAN SAPI LOCAL WISDOM-BASED LKPD ON CRITICAL THINKING SKILLS AND STUDENT LEARNING OUTCOMES - Ach Fauzi; Pramudya Dwi Aristya Putra; Nur Ahmad (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
Critical thinking skills are one of the abilities that students need to have in learning because of the development of science. The formulation of the problem is how the influence of LKPD Based on Local Wisdom Karapan Sapi on critical thinking skills and learning outcomes. The difference from previous research is that local wisdom is chosen to be integrated into science learning. The purpose of this research is to know the effect of LKPD Based on Local Wisdom Karapan Sapi on critical thinking skills and learning outcomes. The method used was Quasi Experiment and then statistical analysis . The result of the t-test data analysis is the value of Sig. (2-tailed) 0.000 <0.05, meaning that there is a significant difference between the experimental class and the control class. LKPD based on local wisdom is very helpful in learning science and aims to build the value of the nation's cultural character.